Evaluating Teaching Effectiveness and Student Performance Across Diverse Courses: An Analysis of Final Exam Scores and Teaching Techniques - Vicente E. Montano; Glenndon C. Sobrejuanite (Journal of Learning Theory and Methodology)
Objectives. This study examines teaching effectiveness and student performance for four business-related courses: Monetary Policy and Central Banking (FM 221), Good Governance and Social Responsibility (BAHR 213), Consumer Behavior (MM 212), and Introduction to Microeconomics (BE 121).